The Function of the Autonomic Nervous System in Asian Patients With Chronic Migraine - Shi, Min; Luo, Danqing; Guo, Jun; Yang, Dongdong; Li, Zhaoying; Zhao, Huan (Frontiers in Neuroscience, 2022)
Background: The pathogenic mechanisms underlying the autonomic nervous system (ANS) dysfunction in patients with chronic migraine (CM) remain unclear. This study investigated the pathogenesis of ANS dysfunction in this population. Methods: A total of 60 patients diagnosed with CM and 60 healthy subjects were recruited to participate in this study. The pupil diameter, pupil contraction velocity, latency, amplitude, and the maximum gradient recovery time were examined before, at 2 min and at 5 min after the cold pressor test, which was combined with the pupillary light reflex method. A brain 3D T1-weighted structural imaging scan, resting-state functional magnetic resonance imaging scan, and diffusion tensor imaging (DTI) scan were also acquired. Results: Patients with CM exhibited a longer recovery time to the maximum gradient at 2 min and at 5 min after cold pressing compared with the control group (P<0.01 and P<0.05, respectively). There was no significant difference in the pupil diameter, pupillary contraction velocity, latency, amplitude, blood pressure, or heart rate between the two groups (all P>0.05). In the CM group, the regional homogeneity (ReHo) values of the left amygdala and left lateral hypothalamic area were significantly higher than those of other brain areas (P<0.001, Alphasim corrected). The DTI scan of the whole brain area showed a lack of significant difference in DTI indices, including FA, MD, AD, and RD values between the two groups (P>0.05, Alphasim corrected). Conclusion: The dysfunction of the left amygdala and left lateral hypothalamic area may be related to ANS dysfunction in patients with CM.